(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study investigated the utilization of e-learning tools as teaching strategies by business educators in tertiary institutions in south east Nigeria. Two research questions were posed and answered while two null hypotheses were formulated and tested at 0.05 level of significance. A descriptive survey design was adopted. A total of 200 business educators in 14 tertiary institutionsin South East, Nigeria made up the population of the study. No sample was taken, as the number was sizeable for the researchers to handle. A structured 25-item validated questionnaire was used for data collection. The reliability of the instrument was ensured using pilot test technique, which was analyzed using Cronbach alpha method and yielded reliability co-efficient of 0.76. Data related to the research questions were analyzed using mean and standard deviation while z-test statistic was used to test the null hypotheses. The findings from the study revealed that multi-media and internet tools were used as teaching strategies but to a moderate extent. The study also revealed that type of institutions do not significantly affect the utilization of e-learning tools (multimedia and internet) as teaching strategies in tertiary institutions in south east, Nigeria. It was concluded that business educators utilized multimedia and internet tools as teaching strategies to a moderate extents as a result of insufficient training and retraining given to them. To encourage the use of e-Learning tools as teaching strategies by business educators, it was recommended, among others, that business educators should develop themselves by inservice training. They should also constantly use e-Learning tools provided by the government and administrators of institutionsin teaching tasks.